Bioavtur Synthesis from Palm Fatty Acid Distillate through Hydrotreating and Hydrocracking Processes - Sabarman, J.S.; Legowo, E.H.; Widiputri, D.I.; Siregar, A.R. (Indonesian Journal of Energy, 2019)
Increasing concern in fossil fuel depletion and CO2 emissions create an urgent need for biofuel substitution. Bio-jet fuel is a possible alternative for conventional jet fuels which currently accounts for 2% of the world’s CO2 emission. Palm Fatty Acid Distillate (PFAD) is the byproduct of palm oil refinery process, which has a potential to become a promising raw material for the synthesis of bioavtur due to its high free fatty acid content. The oil-to-jet pathway is a possible route to produce bioavtur from PFAD, which includes hydrotreating, hydrocracking, and hydroisomerization processes. This research aims to investigate the hydrotreating and hydrocracking processes. The parameters that were investigated are temperature, solvent to PFAD ratio, catalyst loading, and pressure. The parameters variations were as follows: the temperature at 350oC and 400oC, the pressure at 40 bar and 32.5 bar, the solvent to PFAD ratio at 2:1 and 1:1, and the catalyst loading (%wt) at 1%, 2%, and 3%. Presulfided NiMo/?-Al2O3 PIDO 120 1.3 was used for one-step hydrotreating and hydrocracking processes. Results indicated that the 400oC provided better free fatty acid (FFA) conversion. FFA is also almost completely removed when the catalyst used is 3% weight. Solvent to PFAD ratio affected the FFA conversion marginally, while higher catalyst loading (3%) improved the FFA conversion. Gas chromatography results show that the hydrocarbon chains are successfully hydrocracked into C9-C17. The best selectivity of the product to bioavtur range was calculated at 68.99%. Solvent ratio affects the hydrocracking more significantly than the catalyst loading. One sample with temperature operation 400oC and solvent to PFAD ratio 1:1 was in the range of conventional avtur density. With the method used in this study, it can be concluded that PFAD is a promising raw material for bioavtur.